Comparison of Performance Characteristic of A Diesel Engine Using Diesel and Kerosene – Diesel Blend - Nitin Kukreja, Sanjeev Kumar Gupta (International Journal of Advanced Science and Technology, 2020)
The significance of diesel engine for human application is growing day by day. The parameters that are used to operate engine also play a vital role. The fast reduction of fuels and growth in price of petrol or diesel products revived interest among researcher to find out suitable blend. In this experimental investigation, the evaluation of properties of blended kerosene with diesel fuel on the performance characteristics of Kirloskar made four stroke single cylinders engine is done. Studied performance parameters are: specific fuel consumption, exhaust temperature, enthalpy change, mechanical efficiency and brake thermal efficiency. Results of this investigation show that the mechanical efficiency and brake thermal efficiency increases as the concentration of kerosene increases. Graphs in between exhaust temperature with load provide that as the load increases the temperature of exhaust gas also get increased. Furthermore, as the concentration of kerosene increase in kerosene diesel blend the specific fuel consumption decrease